Pengujian Kuat Lentur dan Geser Balok Beton dengan Bundel Tulangan - Rinrin Siti Ratna Purinur; Eko Walujodjati (Jurnal Konstruksi, 2022)
The beam is part of a shear system, generally a horizontal component in the moment frame, responsible for bending and shear forces with or without axial or torsional forces. In construction, problems are often encountered in obtaining structural elements with a small cross-section but having great strength, as well as small reinforcement spacing because of the large area of ​​reinforcement required. The purpose of this study is to obtain a solution for structural elements, especially beams, so that they have great strength with unreachable reinforcement spacing requirements, by knowing the ratio of shear and flexural strength in bundled 4Φ6 reinforced concrete beams and single reinforced concrete beams using the proportion of the cross-sectional area of ​​the reinforcement. the same one. The results of the average compressive strength test of cylindrical concrete for 28 days are f'c 12.68 MPa. The beam with bundle reinforcement (TP 4Φ6) has a cross-sectional area of ​​105.83 mm2 while the beam area with single reinforcement (TP Φ12) has a cross-sectional area of ​​106.80 mm2 so that the cross-sectional area of ​​the reinforcement bundle has a difference of 0.97 mm2 or 0.92 % with single reinforcement. The average flexural strength of TP 4Φ6 beam beam = 9.11 KNm, and Φ12 single beam beam = 7.61 KNm. The average shear strength value of TP bundle reinforcement beams is 4Φ6 = 58.88 KN, and that of single reinforcement beams is Φ12 = 57.94 KN. Beams with bundles of reinforcement produce a difference in flexural strength of 19.71% and a difference in shear strength of 1.62%, so beams with bundles of 4Φ6 reinforcement are stronger than beams with single reinforcement of Φ12.